2015
DOI: 10.1039/c5ra15856g
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular solvent-based microextraction method for cobalt traces in food samples with optimization Plackett–Burman and central composite experimental design

Abstract: A new microextraction method based on formation of supramolecular solvent (Ss) was developed by using of chemometric optimization method for cobalt determination with microsampling flame atomic absorption spectrometry (MS-FAAS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…The preconcentration step involves multiple variables, including type of solid sorbent, volume of sample and eluent, preconcentration and elution flow rate. Univariate studies, in which only one parameter is varied at a time, are widely used to evaluate the efficiency of SPE, providing an approximation of the effect of each variable on the response ; however, the experimental design is gaining increasing importance in the development of analytical methodologies , which enables the delineation of an optimal response and characterization of experimental parameters . The advantages of this statistical approach are the ability to select the optimal experimental conditions with the minimum number of experiments and lowest cost, as well as to evaluate the obtained results to guarantee maximum reliability for the conclusions (http://www.quimica.urv.es).…”
Section: Introductionmentioning
confidence: 99%
“…The preconcentration step involves multiple variables, including type of solid sorbent, volume of sample and eluent, preconcentration and elution flow rate. Univariate studies, in which only one parameter is varied at a time, are widely used to evaluate the efficiency of SPE, providing an approximation of the effect of each variable on the response ; however, the experimental design is gaining increasing importance in the development of analytical methodologies , which enables the delineation of an optimal response and characterization of experimental parameters . The advantages of this statistical approach are the ability to select the optimal experimental conditions with the minimum number of experiments and lowest cost, as well as to evaluate the obtained results to guarantee maximum reliability for the conclusions (http://www.quimica.urv.es).…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of Ni(II) from aqueous sample solution depends on the complexation interaction with the N,N′-Dihydroxy-1,2-cyclohexanediimine ligand, as well as the charge distribution on this ligand which allows the presence of inert tail and facilitate the transference to organic supramolecular phase [16][17][18][22][23][24]. Thus, the volume of introduced 0.1% N,N′-Dihydroxy-1,2-cyclohexanediimine ligand was studied in the range from 50 μL to 300 μL and the calculated recoveries% are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The suitable volume of 0.1% N,N′-Dihydroxy-1,2-cyclohexanediimine ligand was found to be between 100 μL and 200 μL. The composition of the supramolecular solvent mixture was investigated by testing mixtures of tetrahydrofuran with 1-decanol, tetrahydrofuran with undecanol, and tetrahydrofuran with decanoic acid [16,[22][23][24][25][26][27][28] and applying the preconcentration steps. It was found that the recovery% was 98%, 79%, 68% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…SUPRAS are nanostructured solvents obtained from amphiphiles through a self-assembly global process occurring on two scales, nano and molecular. 58,85 The external effects such as pH, electrolyte concentration, and temperature of the sample and the type and amount of solvent are important in the self-assembly global process. In these methods, coacervates consisting of the reverse micelles (size 3-500 nm) of long chain alcohols or carboxylated acids dispersed in an aqueous solution of tetrahydrofuran are injected into the aqueous sample solution.…”
Section: Dispersive Liquid-liquid Microextraction (Dllme)mentioning
confidence: 99%
“…The supramolecular solvents have different kinds of interactions (e.g., hydrogen bonding and hydrophobic) with the analytes in aqueous sample phase for effective mass extraction. 85,86 In 2012, Farajzadeh and Mogaddam provided a new application of the DLLME method called air-assisted liquid-liquid microextraction (AA-LLME). In this method, a lower amount of extraction solvent is used, and there is no need to use a dispersive solvent.…”
Section: Dispersive Liquid-liquid Microextraction (Dllme)mentioning
confidence: 99%